Green And Empowered: Sustainable Business in The Modern Era - Ilyona Risty; Oliandes Sondakh (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
The implementation of Community Service (CS) for the March 2025 period was carried out by a Team from the Faculty of Economics and Business School UPH Surabaya Campus together with Radio Sangkakala Surabaya as partners. Therefore, Universitas Pelita Harapan Surabaya Campus collaborated with Radio Sangkakala Surabaya to be able to provide education to the wider community. This collaboration was built by presenting quality speakers from the Management Study Program and the Accounting Study Program. Each speaker will present interesting topics that are in accordance with current issues. Based on discussions regarding community needs, this CS was carried out by providing supplies to the Community with the theme Green and Empowered. With the holding of this interactive talk show, it is hoped that it can provide information and educational education for the wider community in the Surabaya area in the fields of economics, business and immigrant issues that can improve community knowledge and skills.